BIOETHANOL PRODUCTION FROM CASSAVA PEELS USING (Candida tropicalis AND Pichia caribbica) - Abdullahi. Y.; Oseni W, S.; Abubakar, A. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2018)
The studies were conducted on the production f ethanol, isolation and identification of two yeast strain from Cola acuminata and Zea mays, using spread plate technique. Physiological, morphological and cultural characteristic of C. tropicalis and P. caribbica were carried out such as sugar assimilation and fermentation test resulting in the discovery of the yeast species. Two isolates belonging to different genera which include Candida tropicalis and Pichia caribbica were used for the fermentation of a particular substrate (cassava peels). The pretreatment of the cassava peels was carried out by chemical hydrolysis followed by the process of distillation of water and ethanol mixture. It was discovered that Pichia caribbica have higher ethanol yield 14.8% in (100g) of substrate of cassava peels than Candida tropicalis which have ethanol yield 10.2% in the same (100g) used for both fermentation. The proximate and elemental analysis of the cassava peel revealed high tendency of ethanol production based on the values obtained. Hence this study indicates that cassava peels can be a good feedstock for sustainable bioethanol production.